Neoadjuvant Chemotherapy and Expandable Prosthesis Reconstruction to Treat Osteosarcoma around the Knee in Children. Issue 1 (20th November 2022) - Huang, Junqi; Cheng, Jiajia; Bi, Wenzhi; Xu, Meng; Jia, Jinpeng; Han, Gang; Wang, Wei
Abstract : Objective: Survival and reconstruction in osteosarcoma is quite challenging. The study aimed to investigate the prognosis in patients treated with neoadjuvant chemotherapy and determine the clinical outcomes of expandable endoprosthesis reconstruction in children. Methods: From January 2009 to December 2014, we retrospectively analyzed 29 skeletally immature children (mean age, 10.5 years; range, 6–15 years) with osteosarcoma around the knee. Of the 29 patients who underwent neoadjuvant chemotherapy and limb salvage surgery, an expandable prosthesis was implanted for reconstruction. No patients were missed during follow‐up. The evaluation index involved follow‐up time, complication, functional results, and lengthening procedures. The survivorship and recurrence were assessed by GraphPad Software, and the function was evaluated by the Musculoskeletal Tumor Society (MSTS) scoring system. Results: A mean follow‐up time was 8.9 years (range, 6–12 years), and the overall 5‐year survival was 89.1% based on Kaplan–Meier analysis. Three patients suffered a relapse and one underwent amputation. Lung metastasis developed in one patient. At 6 months after the operation, patients had a mean MSTS score of 27 points (range, 24–29). Two patients underwent revision surgery, one for implant infection and one for aseptic loosening. Prognosis is correlated with alkaline phosphatase change after treatment. Conclusions: Chemotherapy scheme and limb salvage can achieve high survival rates. This expandable prosthesis was associated with good function and low complication rates. The character of expandability could be a method to overcome discrepancies in the growth period. Abstract : The expandable devices were made up of titanium alloy. This technique overcomes discrepancy and reduces risk of invalid gears.